Data processing strategies to determine maximum oxygen uptake: a systematic scoping review and experimental comparison with guidelines for reporting - Nolte, S.; Rein, R.; Quittmann, O. J. (Sports Medicine, 2023)
Background: Gas exchange data from maximum oxygen uptake ( .V O 2 max ) testing typically require post-processing. Different processing strategies may lead to varying .V O 2 max values affecting their interpretation. However, the exact processing strategies used in the literature have yet to be systematically investigated. Previous research investigated differences across methods at the group level only. Methods: Out of a random sample, we investigated 242 recently published articles that measured .V O 2 max during ramp tests. Reported data processing methods and their rationale were extracted. We compared the most common processing strategies on a data set of 72 standardized exercise tests in trained athletes. Results: Half of the included studies did not report their data processing strategy and almost all articles failed to provide a rationale for the particular strategy chosen. Most studies use binned time averages to determine .V O 2 max , with a minority using moving time or moving breath averages. The processing strategies found in the literature can lead to mean differences in .V O 2 max of more than 5% (range 0.7%) with considerable variation at the individual level. Conclusions: We advise researchers to change their processing strategy and use moving averages or digital filters instead of binned averages. Researchers should report their data processing strategy used to determine .V O 2 max . We provide a reporting checklist of seven items that can function as a template for reporting.